EU FACING ILLEGAL IMMIGRATION, THE ROAD TO EU - Cara, Arben; Margjeka, Mimoza (European Scientific Journal, ESJ, 2015)
The problem of illegal immigration has being a growing concern within the EU. The European Union has always been hocked in the struggle against clandestine immigration. From the Council of Tamper in 1999, the member states are hocked to fight against clandestine immigration. Large numbers of people moves across the borders of the EU for the sake of job opportunities. Sometimes, people cross the border independently, while other times, they do so collectively with other people. The corrupt custom officers and police are strong facilitators of this illicit immigration of these people. Also, the need for people is exploited by an organized crime groups operating in this field. Illegal immigration and trafficking of human beings are combined activities of organized crimes. These can be seen mostly as a labor market problem, and the EU is trying to frame a policy regulating both labor markets and migratory flows. This therefore constitutes the main aim of this study.